Physiological role of plasma and its components and the clinical implications of different methods of apheresis: A narrative review. Issue 3 (26th August 2020) - Ahmadpoor, Pedram; Aglae, Cedric; Cariou, Sylvain; Pambrun, Emilie; Renaud, Sophie; Garo, Florian; Darmon, Ruben; Schultz, Celine; Prelipcean, Camelia; Reboul, Pascal; Moranne, Olivier
Abstract: Nowadays, therapeutic plasmapheresis (TP) is accepted as part of the treatment for specific groups of diseases. The availability of different methods, including double filtration and adsorption, increases selectivity for the removal of substances. However, the use of these techniques requires a thorough understanding of the characteristics and components of plasma. By considering pivotal papers from several databases, the aim of this narrative review is to describe the characteristics of plasma related to apheresis techniques. We have tried to cover the clinical implications including physiology, estimation of plasma volume, viscosity, and a description of its components including the size, volume of distribution, and half‐lives of the different substances to be removed or maintained depending on the clinical situation and applied apheresis technique. Applying this knowledge will help us to choose the right method and dosage and improve the efficacy of the procedure by preventing or addressing any complications.